Innovative models of opera performance in the context of creating user experience – example of the opera La Traviata - Krajnović, Aleksandra; Gortan-Carlin, Ivana Paula; Morović, Žan (Oeconomica Jadertina, 2023)
This paper deals with the paradigm of the economy of experience in the activities of the cultural sector - music and performing arts, an area that has not been sufficiently explored in the scientific literature. The paper gives a brief overview of the contextual framework of the economy of experience in the field of musical art. On the specific, innovative example of the opera performance of Giuseppe Verdi's La traviata, which was performed in Zadar in 2008, and designed and realized by the co-author of this paper (Morović, 2008), the characteristics of the user experience are analyzed by verifying the experience economy model through the characteristics of the experience in the model of Boswijk and associates (2006). A qualitative analysis of the case study was applied, based on which the author's own model was created and presented in the paper, which belongs to the field of audience development in culture and art. The scientific contribution of the paper is manifested in the search for answers to what extent innovative models of musical performance meet the principles of creating an authentic user experience in the experience economy. The author's own model of the '4E kingdom' of Pine and Gilmore is introduced using the example of opera. Furthermore, with their paper, the authors contribute to defining the conceptual framework in the research area of connecting musical art and user experience in the context of the experience economy. The authors believe that this is particularly important in order to bring works of art closer to a wider audience, especially young people. Innovative models of musical performance, according to the authors, are those that, in addition to traditional performances of opera in theaters and opera houses, can offer an additional 'product' with a refined and expanded experience of music, which will encompass all five senses and remain in the memory of the recipients as an unforgettable experience.
Keywords: experience economy, 4E model, innovative models of musical performance, user experience in culture, opera, audience development